Pemetaan Penggunaan Lahan Dusun Sukamaju Desa Natar Kabupaten Lampung Selatan - Anisa, Rahma; Citra Dewi; Fauzan Murdapa; Eko Rahmadi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Inovatif, 2024)
Natar Village is located in Natar District, South Lampung Regency which is divided into several hamlets, one of which is Sukamaju Hamlet which is a hamlet that is experiencing rapid development because it is a strategic area where there are several facilities. In recent years, there have been changes in land use in this hamlet, such as the expansion of agricultural land, housing developments, and other activities. To understand and manage land use effectively and sustainably, it is necessary to carry out comprehensive land use mapping. Therefore, the technical team plans to carry out land use mapping activities using Satellite Imagery. This activity aims to carry out land use mapping and understand land use trend patterns in the area. The mapping method used is an on-screen digitized guided classification based on 9 key image interpretations. The results of the service in Sukamaju Hamlet are a 1:3000 scale land use map product consisting of a residential area of 17.76 ha, plantations of 5.35 ha, rice fields of 0.85 ha, and a road length of 10,452.16 m and waters of 2,686.40 m. This of course influences the trend pattern in areas dominated by residential land. This land use map can provide the latest information regarding the development of sustainability areas in Sukamaju Hamlet for village officials and residents.